Human rights in states of emergency in international law - Oraa, Jaime (Oxford : Clarendon Press, 1992)
"Revised version of a thesis submitted in January 1990 for the degree of Doctor of Philosophy at Oxford University."--Acknowledgement
Keywords: Human rights; International law; Treaties; War and emergency legislation